Development of Saline and Alkaline Soils in the Chambal Command and Suggestions for their Reclamation - Dayal, Rajbans; singh, Gurmel; Nambiar, KK (Journal of Soil and Water Conservation, 2022)
With the introduction of irrigation through canal system, it has been observed that 40,000 acres of land have become water logged with a water table within 5 ft., while 1,10,000 acres of land within 5 ft. to 10 ft. from the surface within a period of three years. The water logging has given rise to salinity and alkalinity in varying degrees in these regions, which in turn, gradually become salty lakes sustaining nothing but salt loving plants. Thus millions of acres of land, which were once the granary of the nation, are converted into waste lands. This wastage of lands in a country like India can not be ignored, as there are very limited agricultural lands. Further, the ever increasing additional mouths are to be fed from the limited resources. The limited fertile lands ’mild: are about to go out of plough are to be protected from water logging, salinity and alkalinity due to irrigation which can undoubtedly be brought under control.